Preclinical efficacy of African medicinal plants used in the treatment of snakebite envenoming: a systematic review protocol. (February 2022) - Bala, Auwal A.; Mohammed, Mustapha; Umar, Saifullahi; Ungogo, Marzuq A.; Hassan, Mohammed Al-Kassim; Abdussalam, Umar S.; Ahmad, Mubarak Hussaini; Ishaq, Daha U.; Mana, Dillos; Sha'aban, Abubakar; Jatau, Abubakar I.; Jibril, Murtala; et al.
Background: Snakebite envenoming (SBE) is a high-priority, neglected, tropical disease that affects millions of people in developing countries annually. The only available standard drug used for the treatment of SBE is antisnake venom (ASV) which consists of immunoglobulins that have been purified from the plasma of animals hyper-immunized against snake venoms. The use of plants as alternatives for treatment of poisonous bites particularly snakebites is important in remote areas where there might be limited, or no access to hospitals and storage facilities for antivenom. The pharmacological activity of some of the medicinal plants used traditionally in the treatment of SBE have also been scientifically validated. Method: A systematic review will be conducted according to the Collaborative Approach to Meta-Analysis and Review of Animal Data from Experimental Studies checklist for study quality in animal/ in vivo studies. The tool will be modified and validated to assess in vitro models and studies that combine in vivo and in vitro studies. The systematic review will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. English published articles on African medicinal plants used in the treatment of snakebite envenoming will be searched in Medline, Embase, and Scopus from 2000 to 2021. Dissemination: The findings of the study will be communicated through publication in peer-reviewed journal and presentation at scientific conferences. Medicinal plants have been important sources for the development of many effective drugs currently available in orthodox medicine. Botanically derived medicines have played a major role in human societies throughout history. Plants components used in traditional medicine gained much attention by many toxinologists as a tool for designing potent antidotes against snake envenoming. Our systematic review will provide a synthesis of the literature on the efficacy of these medicinal plants. We will also appraise the prospects of African medicinal plants with pharmacologically demonstrated activity against snakebite and envenoming.